Immigration in America : asylum, borders, and conflicts - Smith-Llera, Danielle, 1971- (Informed! (North Mankato, Minn.), 2020)
Explores the different issues surrounding immigration and border security in the United States including what immigration should be allowed, what should happen to the DREAMers, and how will a border wall help or hinder the immigration process.